Laparoscopic surgery for a Bochdalek hernia triggered by pregnancy in an adult woman: A case report. (2018) - Matsudera, Shotaro; Nakajima, Masanobu; Takahashi, Masakazu; Muroi, Hiroto; Kikuchi, Maiko; Shida, Yosuke; Ihara, Keisuke; Yamaguchi, Satoru; Sasaki, Kinro; Tsuchioka, Takashi; Kato, Hiroyuki
Highlights: We report a case of Bochdalek hernia (BH) triggered by pregnancy in a pregnant adult. Laparoscopic surgery can be safely performed for BH without complications. We reviewed 30 cases of laparoscopic and/or thoracoscopic repair of adult BH. Abstract: Introduction: A Bochdalek hernia (BH) is a type of congenital diaphragmatic hernia. We herein describe an adult woman with a BH triggered by pregnancy and treated by laparoscopic surgery. Presentation of case: A 26-year-old woman was referred to our hospital because of abdominal pain and dyspnea resulting from a left diaphragmatic hernia. She was diagnosed with a BH and underwent laparoscopic surgery. Her postoperative progress was satisfactory, and no recurrence was found at follow-up approximately 1 year later. Discussion: A recently published study reviewing detailed cases of laparoscopic and/or thoracoscopic repair of adult BH from 1999 to 2016 identified 30 cases. A laparoscopic approach for treatment of BH has recently attracted increasing interest. Conclusion: Laparoscopic surgery can be safely performed on adults with BH without complications.